Civil War cooking the Union - Dosier, Susan (North Mankato, Minnesota Capstone Press, 2017)
Discusses the everyday life, cooking methods, foods, and celebrations of Union soldiers during the Civil War. Includes recipes and sidebars"--
A gift from book Africa
Cooking
1 2 11 13
NEW_ZTN_GN
Keywords: Cooking, American -- History -- Juvenile literature; Food habits -- United States -- History -- 19th century -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Juvenile literature